Foaming properties and olfactory profile of fermented chickpea aquafaba and its application in vegan chocolate mousseMendeley Data - Lea Mehren; Lena Elliger; Hanna May; Andreas Schieber; Nadine Schulze-Kaysers (Current Research in Food Science)
Aquafaba, the cooking water of chickpeas and other pulses, is used as a vegan egg white substitute because of its favorable technofunctional properties. Nonetheless, its application is often restricted by a “beany” flavor and poor foaming properties compared to egg white. To overcome these limitations, aquafaba was fermented with two edible basidiomycetes. During the fermentation process, foaming properties were measured and analyzed. Furthermore, the aroma change was described by sensory experts. Based on these results, the optimal fermentation day was selected for each mushroom and sensory profiling was conducted. Subsequently, chocolate mousse was prepared from fermented aquafaba and profiled as well as tested in an acceptance test. Aquafaba profiling revealed significantly lower scores (α = 5%) for “beany” odor in fermented samples. Chocolate mousse produced with fermented aquafaba was described as less “beany” but more “chocolatey” and “cocoa-like” in smell and taste, and more “sweet” in taste. The texture of mousse prepared with fermented aquafaba was more “fluffy/light/porous” and “soft” but less “homogenous” than mousse with unfermented aquafaba. The consumer test showed high overall liking for all mousses. The research described in this study revealed for the first time promising aroma changes based on fermentation in aquafaba and demonstrated improved foaming properties. Thus, fermentation can be considered a useful tool to enhance the quality of aquafaba and thus expand its fields of application.